Comparative Neurologic Outcomes of Salvage and Definitive Gamma Knife Radiosurgery for Glomus Jugulare: A 20-Year Experience - Wakefield, Daniel V.; Venable, Garrett T.; VanderWalde, Noam A.; Michael, L. Madison, II; Sorenson, Jeffery M.; Robertson, Jon H.; Cunninghan, David; Ballo, Matthew T. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objective This case series investigates management of glomus jugulare (GJ) tumors utilizing definitive and salvage Gamma Knife stereotactic radiosurgery (GKSRS).Methods A retrospective chart review was performed to collect data. Statistical analysis included patient, tumor, and treatment information.Results From 1996 to 2013, 17 patients with GJ received GKSRS. Median age was 64 years (range, 27–76). GKSRS was delivered for definitive treatment in eight (47%) and salvage in nine (53%) patients. Median tumor volume was 9.8 cm3 (range, 2.8–42 cm3). Median dose was 15 Gy (range, 13–18 Gy). Median follow-up was 123 months (range, 38–238 months). Tumor size decreased in 10 (59%), stabilized in 6 (35%), and increased in 1 patient (6%). Overall neurological deficit improved in 53%, stabilized in 41%, and worsened in 6% of patients. Overall cause-specific survival was 100%, and actuarial local control was 94%. Eighty-eight percent of patients without prior resection experienced neurologic deficit improvement, while 25% of patients with prior resection experienced neurologic improvement (p = 0.02).Conclusion Gamma Knife radiosurgery provides effective long-term control of GJ and overall improvement or stabilization of neurological deficit in most patients. Patients with prior resection are less likely to experience improvement of neurologic deficit.
Keywords: glomus jugulare; Gamma Knife; radiosurgery; salvage